Living in the vicinity of pesticide-treated crop fields: Exploring associated perceptions and psychological aspects in relation to self-reported and registry-based health symptoms - J Gerbecks; C Baliatsas; CJ Yzermans; M Simoes; A Huss; RA Verheij; MLA Dückers (BMC Psychology)
Abstract Background Exposure to pesticides in the living environment can be associated with the prevalence of health symptoms. This study investigates associations between health symptoms among residents in areas with fruit crop fields where pesticides are applied, and psychological perceptions and attitudes about environmental aspects and exposures. Methods A cross-sectional survey combined with routine primary care electronic health records (EHR) data was conducted in 2017 in rural areas of the Netherlands with high concentration of fruit crops (n = 3,321, aged ≥ 16 years). Individual exposure to pesticides was estimated using geocoded data on fruit crops around the home. Validated instruments were used to assess symptom report and psychological perceptions and attitudes. Annual prevalence of various health symptoms was derived from EHRs. Multilevel regression models were used to analyze associations between health symptoms (outcome), fruit crops, and multiple psychological perceptions and attitudes (confounders). Results Living in the vicinity of fruit crop fields was generally not associated with self-reported symptom duration and general practitioner (GP) registered symptoms. For self-reported symptoms, symptom prevalence decreased when crop density within 250 m and 500 m from the home increased. No associations were found at other distances. Furthermore, higher levels of environmental worries, perceived exposure, and perceived sensitivity to pesticides and attribution of symptoms to environmental exposures were generally associated with a higher number of self-reported symptoms, and longer symptom duration. Symptoms reported to GPs were not associated with psychological perceptions and attitudes, except for perceived sensitivity to pesticides. Conclusion Psychological perceptions and attitudes appear to be related to self-reported symptoms, but not to GP-registered symptoms, independent of the actual levels of exposure as measured by the size of the area of crop fields. Perceptions about environmental factors should be taken into account in environmental health risk assessment research when studying health symptoms.